PTU-142 A Cost-Effectiveness Analysis for Radiofrequency Ablation (RFA) in The Treatment of Patients with Barrett's Oeosphagus Related Neoplasia in the United Kingdom. (17th August 2016) - Filby, A; Taylor, M; Lipman, G; Haidry, R
Abstract : Introduction: Barrett's oesophagus (BE) is the precursor lesion to osophageal adenocarcinoma (OAC) which carries a poor 5 year survival. BE progresses in patients through a metaplasia, dysplasia to cancer sequence. There is now consensus from worldwide societies to target the disease when there is dysplasia as these patients will develop invasive cancer in up to 50% of cases if left untreated. Treatment is now firmly established as minimally invasive endoscopic therapy with a combination of endoscopic resection for visible dysplasia surgery with oesophagectomy which can carry a significant mortality and morbidity. The aim of this analysis was to evaluate the cost-effectiveness of treating patients with HGD arising in BE with endoscopic therapy compared with surveillance alone in the UK. Methods: A cost-effectiveness model was developed from an NHS perspective. The model structure consisted of a decision tree and a modified Markov model. The model considers a cohort of HGD patients and takes a lifetime time horizon. Patients move through the health states in the model (no dysplasia, low-grade dysplasia, HGD and OAC) based on natural history data (including progression and regression). HGD patients in the treatment arm are treated with RFA (plus EMR in a proportion of cases), LGD patients receive surveillance only. When patients are successfully treated with RFA they move to the 'no dysplasia' health state in the model and can progress again in the future. If treatment is not successful, the patient remains in the same health state in which they started treatment. In the comparator arm, all patients receive surveillance only. In both arms, when patients progress to OAC, patients are treated with oesophagectomy. Treatment with oesophagectomy can result in treatment success or death. The model inputs were derived from published literature, clinical expert opinion and standard cost sources. Results: The results estimated that, at a time horizon of 45 years, providing HGD patients endoscopic treatment with RFA compared to endoscopic surveillance until cancer developed resulted in additional costs of £3, 939. Patients benefitted from additional quality-adjusted life years (QALYs) of 0.954 per patient. The incremental-cost effectiveness ratio is £4, 128. This would be considered cost-effective using the threshold of £20, 000 to £30, 000 used by NICE. Conclusion: The economic model estimates that treating patients with BE related HGD with endoscopic treatment and RFA would be a cost efficient use of NHS resources and endorses the view of the British Society Of Gastroenterology advising this is as the standard of care in these patients. Disclosure of Interest: A. Filby Consultant for: Medtronic, M. Taylor Consultant for: Medtronic, G. Lipman: None Declared, R. Haidry: None Declared